Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð³Ð¸Ð¿Ð¾Ñ‚ÐµÑ€Ð¼Ð¸Ñ‡ÐµÑÐºÐ¾Ð³Ð¾ Ñ…Ñ€Ð°Ð½ÐµÐ½Ð¸Ñ Ð´Ð¾ Ð¸ Ð¿Ð¾ÑÐ»Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ Ð½Ð° ÑÐ²Ð¾Ð¹ÑÑ‚Ð²Ð° ÑÐ´ÐµÑ€Ð½Ñ‹Ñ… ÐºÐ¾Ð¼Ð¿Ð¾Ð½ÐµÐ½Ñ‚Ð¾Ð² Ð¸ Ð¿Ð»Ð°Ð·Ð¼Ñ‹ Ñ†ÐµÐ»ÑŒÐ½Ð¾Ð¹ ÐºÐ¾Ñ€Ð´Ð¾Ð²Ð¾Ð¹ ÐºÑ€Ð¾Ð²Ð¸ Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° - Tsutsayeva, A. A.; Tsyganenko, A. Ya.; Zheltyakova, I. A.; Brovko, E. V.; Glushko, T. A.; Rozanova, E. D. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
There were presented research results of hypothermic storage duration influence of whole human cord blood before and after cryopreservation on morphofunctional parameters, cryostability of its nucleated components and virus-neutralizing plasma properties. There was shown that at hypothermic storage stage, depending on its duration, non-lethal damages of nucleated cells appeared. Maximal admissible term of hypothermic storage of human cord blood makes 24 hrs before cryopreservation and not more than 2 hrs after it. At hypothermic storage stages and after cryopreservation virus-neutralizing activity of human cord blood plasma does not statistically and significantly change.